Bioprospecting of marine invertebrates for new natural products - a chemical and zoogeographical perspective - Leal, Miguel Costa (2019)
Bioprospecting for new marine natural products (NPs) has increased significantly over the last decades, leading to an unprecedented discovery of new molecules. Marine invertebrates have been the most important source of these NPs, with researchers commonly targeting particular taxonomic groups, marine regions and/or molecules from specific chemical groups. The present review focuses on new NPs identified from marine invertebrates between 2000 and 2009, and performs a detailed analysis on: (1) the chemical groups of these NPs; (2) the association of particular chemical groups to specific marine invertebrate taxa; and (3) the yielding of molecules from the same chemical group from organisms occurring in a particular geographic region. Our survey revealed an increasing number of new terpenoids being discovered between 2000 and 2009, contrasting with the decreasing trend in the discovery of new alkaloids and aliphatic molecules. Overall, no particular association was identified between marine invertebrate taxa and chemical groups of new NPs. Nonetheless, it is worth noting that most NPs recorded from cnidarians and mollusks were terpenoids, while most NPs identified in echinoderms were aliphatic compounds or carbohydrates. The geographical trends observed in our study do not support the idea of particular chemical groups of new NPs being associated with marine invertebrates from any specific geographical region, as NPs from different chemical groups were commonly distributed worldwide.